PERAN KEPALA SEKOLAH DALAM KEGIATAN SUPERVISI AKADEMIK DI MADRASAH TSANAWIYAH NEGERI DAN MADRASAH TSANAWIYAH MUHAMMADIYAH SUNGAI APIT - Nartam Nartam; Isjoni Isjoni; Murni Baheram (Universitas Riau, 2020)
This study has a purpose to obtain information about the role of headmaster in academic supervision activities at MTS Negeri and MTS MuhammadiyahSungai Apit. Which one includes the role of human resource developers, curriculum developer, mediator of relationships among the citizens in school and the role of administration. Data collection technique in this research include is interview, observation and documentation study. Interviews were conducted with the headmaster as core informants and vice of headmaster, teachers and school supervisors as control information. Observation is done by observing the role of principal in academic supervision activities. Documentation of study is data collection that analyzes documents relating to the principal's role in academic supervision activities. The result of the research shows that the principal of MTS Negeri and MTS Muhammadiyah has performed its role as human resource developer, curriculum developer, mediator of relationship among school people and asadministration in academic supervision activity in each school.